The Otanes dilemma in Latin America - Mario Gustavo Berrios Espezúa (2019)
The prominent Italian political scientist Norberto Bobbio (1909-2004) wrote a very interesting book about the forms of government in the history of political thought (Bobbio, 1992), in that book he begins with a "famous discussion" between three Persian characters: Otanes, Megabyzo and Dario, about what should be the best form of government to be established in Persia. Otanes is the defender of the government of many (democracy), Megabyzo defends the government of a few (aristocracy) and Dario defends the government of one (monarchy), Otanes democracy is the only form of government that guarantees equality before the law. During the study of forms of government (from Plato to Marx), Bobbio comes to the conclusion that the best form of government of all is democracy; however, in Latin America, democracy has assumed different tones and even some non-democratic forms of government pass themselves off as democratic. In this paper we will develop some points referring to the famous discussion that Bobbio reviews and its importance in the current debate about the best form of government in Latin America; second, we will present the neoliberal context in which democracy in Latin America was established at the beginning of the 21st century; next, we will comment on some data about democracy in three countries of the region: Venezuela, Ecuador and Peru.